2009
DOI: 10.1136/ard.2007.085753
|View full text |Cite
|
Sign up to set email alerts
|

C4b-binding protein (C4BP) inhibits development of experimental arthritis in mice

Abstract: Objectives:To assess the human complement inhibitor C4b-binding protein (C4BP) for treatment of arthritis.Methods:We have used two mouse models of rheumatoid arthritis (RA) to assess the therapeutic effect of C4BP on different phases of arthritis, the collagen antibody-induced arthritis (CAIA), an acute antibody-induced disease and the collagen-induced arthritis (CIA), which carries the full complexity of arthritis.Results:Purified human C4BP injected intraperitoneally alleviated CAIA significantly in a manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…injection of human C4BP induced a low level of complement inhibition, it was able to significantly inhibit the development of experimental arthritis in mice (15). Thus, our study could provide a possible mechanism explaining the in vivo effect of C4BP(b 2 ) regulating autoim- …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…injection of human C4BP induced a low level of complement inhibition, it was able to significantly inhibit the development of experimental arthritis in mice (15). Thus, our study could provide a possible mechanism explaining the in vivo effect of C4BP(b 2 ) regulating autoim- …”
Section: Discussionmentioning
confidence: 84%
“…It has been recently reported that i.p. administration of human C4BP was able to inhibit the development of autoimmune arthritis in mice, although it was only moderately affecting complement activity (15). This suggests that other mechanisms might be involved in the anti-inflammatory activity of C4BP.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In RA, complement activation is triggered by immune complexes, apoptotic/ necrotic cells, and released cartilage components, which results in further activation of components of both the innate and adaptive immune system due to the interaction of complement activation products and their receptors on target cells. A number of studies have demonstrated beneficial effects of complement inhibition at the level of C3-convertase (20) or C5a generation (21,22) in murine models of RA. Formation of MAC has FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…Deposited autoantibodies, immune complexes, apoptotic cells, and necrotic cells can activate this cascade, leading to the release of proinflammatory activators, recruitment of inflammatory cells (Figure 1), and formation of membrane attack complexes. The levels of complement activation components are elevated in the synovial fluid, synovium, and cartilage of patients with arthritis (19)(20)(21)(22)(23), and targeted deletion/inhibition reduces disease severity in murine arthritis models (7,24,25). These previous studies have led to the development of therapeutic approaches targeting complement components for the treatment of RA (for review, see ref.…”
Section: Complement Cascadementioning
confidence: 99%